PERANCANGAN PROTOTYPE VIRTUAL MUSEUM KERATON KASUNANAN SURAKARTA HADININGRAT BERBASIS WEB - Stefanie G.N.L. Worang; Michael Bezaleel Wenas; T. Arie Setiawan Prasida; Andeka Rocky Tanaamah (Jurnal Informatika, 2015)
Museum of Keraton Kasunanan Surakarta Hadiningrat is a museum located in Solo that saves a lot of cultural heritage objects of Java. But the limitation of time, cost, and location cause not everyone can see directly the objects, so the access to that objects are limited. Prototype Virtual Museum Keraton Kasunanan Surakarta Hadiningrat which utilize Web-based 3D Web Technology is expected to increase public accessibility to the historical objects as well as instructional media and the delivery of information interesting and interactive in order to preserve the cultural heritage and the development of Java.